Increasing Pain Sensation Eliminates the Inhibitory Effect of Depression on Evoked Pain in Rats - Wang, Ning; Li, Sheng-Guang; Lin, Xiao-Xiao; Su, Yuan-Lin; Qi, Wei-Jing; Wang, Jin-Yan; Luo, Fei (Frontiers in Behavioral Neuroscience, 2016)
Although previous studies have suggested that depression may be associated with inhibition of evoked pain but facilitation of spontaneous pain, the mechanisms underlying these relationships are unclear. The present study investigated whether the difference between evoked and spontaneous pain on sensory (descending inhibition) and affective (avoidance motivation) components contributes to the divergent effects of depression on them. Depressive-like behavior was produced in male Wistar rats by unpredictable chronic mild stress (UCMS). Tone-laser conditioning and formalin-induced conditioned place avoidance (F-CPA) were used to explore avoidance motivation in evoked and spontaneous pain, respectively. Behavioral pharmacology experiments were conducted to examine descending inhibition of both evoked (thermal stimulation) and spontaneous pain behavior (formalin pain). The results revealed that the inhibitory effect of depression on evoked pain was eliminated following repeated thermal stimuli. Avoidance behavior in the tone-laser conditioning task was reduced in UCMS rats, relative to controls. However, avoidance motivation for formalin pain in the UCMS group was similar to controls. 5-HT1A receptor antagonism interfered with inhibition of pain responses over time. The present study demonstrated that the inhibitory effect of depression on evoked pain dissipates with increased nociception and that the sensory-discriminative and affective-motivational components of pain are jointly involved in the divergent effects of depression on pain.